Counseling on the Use of Organic Waste in Realizing Sustainable Development in Villages - Amruddin, Amruddin; Hamidah, Emmy; Suparwata, Dewa Oka; Utami, Cahyaning Rini; Hertini, Etty Sri (Universitas Pahlawan Tuanku Tambusai, 2024)
Biringala Village is one of the villages in Barombong District, Gowa Regency, South Sulawesi. Geographically, the location of Biringala Village is very strategic because Biringala Village is one of the supporting villages for the Economic Zone in Gowa Regency, South Sulawesi. The current problem faced by Biringala village is environmental problems, this is due to the lack of public awareness about waste management, besides that infrastructure such as waste transport fleets as well as TPA (Final Disposal Site) and TPS (Trash Disposal Site) are still very limited. To overcome this problem, one alternative solution that can be implemented is by holding activities to manage the use of organic waste in realizing sustainable development in Biringala Village, Barombong District, South Sulawesi Regency. Therefore, the aim of this community service is to see the potential of using organic waste in realizing sustainable development in Biringala Village, Barombong District, South Sulawesi. To obtain the data used were observation and literature review. This service activity is an educational effort on the use of organic waste in Biringala Village, Barombong District, Gowa Regency, South Sulawesi. As a form of the author's thinking, several efforts and breakthroughs are offered, namely: 1.) Increasing community knowledge and community income who already know that organic waste can be utilized so that it can create sustainable community welfare, 2.) The role of using organic waste for the people of Biringala Village in realizing sustainable village development is to improve the quality of life to be cleaner and Healthy.